Smart home hacks - Meyer, Gordon (Hacks series., 2005)
So much of what is commonplace today was once considered impossible, or at least wishful thinking. Laser beams in the operating room, cars with built-in guidance systems, cell phones with email access. There's just no getting around the fact that technology always has, and always will be, very cool. But technology isn't only cool; it's also very smart. That's why one of the hottest technological trends nowadays is the creation of smart homes. At an increasing rate, people are turning their homes into state-of-the-art machines, complete with more switches, sensors, a.